Communication Strategies to Prevent Terrorist Group’s Radical Ideology and Doctrine within Islamic Universities at Central Sulawesi - Muhammad Khairil (Al-Ulum, 2017)
The development of terrorist groups continues to undergo metamorphosis through the transformation of the communication network and radicalism doctrine. This phenomenon makes affiliation efforts with radical groups, including building networks in the higher education. Radical Ideas easily penetrate campuses and universities. The vulnerability is not only seen from a psycho-social approach alone, but also as in instrument or media that outspread hatred and violence that designed to fit campus lifestyle. Some of the ways are such as books, magazines, bulletins, internet and social media networks. Universities can formulate appropriate and effective communication strategies as an effort in de-radicalisation, indoctrination, and de-ideologisation. Altering Islamic stigma as a terrorist religion and eliminating the image of Indonesia as implementing the teachings of Islam substantively according to Indonesian Islamic localities can do a terrorist country. Islam penetrated and developed in Indonesia not based on violence or religious radicalism, but by reflecting the spirit of Islam as the religion of blessing to the world (rahmatan lil alamin).